Association Between Family History, a Genetic Risk Score, and Severity of Coronary Artery Disease in Patients With Premature Acute Coronary Syndromes. Issue 6 (June 2016) - Hindieh, Waseem; Pilote, Louise; Cheema, Asim; Al-Lawati, Hatim; Labos, Christopher; Dufresne, Line; Engert, James C.; Thanassoulis, George
Abstract : Objective—: A genetic risk score (GRS) for coronary artery disease has recently been shown to be independent of family history (FHx) in predicting future cardiovascular events. We sought to determine whether the presence of these risk factors, either individually or together, was associated with a higher burden of angiographic coronary artery disease. Approach and Results—: We included 763 patients with premature acute coronary syndrome (median age, 50 [46–53] years; 30.8% women) with at least 1 major epicardial vessel stenosis enrolled in the Gender and Sex Determinants of Cardiovascular Disease From Bench to Beyond in Premature Acute Coronary Syndrome (GENESIS-PRAXY) study, a multicentre prospective cohort study of premature patients with acute coronary syndrome (aged ⩽55 years). The prevalence of multivessel disease (ie, ≥2 vessels with >50% stenosis) in individuals with FHx was 49.7% as compared with 37.9% in those without FHx ( P <0.01 for comparison). In adjusted models for age, sex, traditional risk factors, and GRS, FHx was associated with a higher prevalence of 3-vessel disease (odds ratio [OR], 1.42; 95% confidence interval, 0.91–2.21; P =0.12 for 2-vessel disease and OR, 2.26; 95% confidence interval, 1.29–3.95; P =0.005 for 3-vessel disease). Individuals with a high GRS were also more likely to have multivessel disease (OR, 1.41; 95% confidence interval, 1.01–1.99; P =0.047) after adjustment for traditional risk factors, including FHx. Individuals with both a FHx and a high GRS as compared with those with neither had the highest ORs for multivessel disease (adjusted OR, 2.14; 95% confidence interval, 1.24–3.69; P =0.0064). Conclusions—: In patients with premature acute coronary syndrome, the presence of either a high GRS or FHx is associated with greater severity of coronary artery disease at angiography. Whether preventive strategies targeted to genetically predisposed individuals will reduce the burden of early acute coronary syndrome warrants further study. Abstract : Supplemental Digital Content is available in the text.